Production and physicochemical characterisation of bio-oil from the pyrolysis of Jatropha curcus waste - Jourabchi, Seyed Amirmostafa (2015)
The increasing use of fossil fuels and the impending depletion of their reserves worldwide are driving alternative energy sources as one of the foremost consideration for research in energy, fuel, and power technology. Additionally, the increasing rate of harmful emissions especially carbon dioxide from the increased usage of fossil fuels have led to the need for more environmentally friendly replacement fuels. Presently, bio-oil originating from biomass has been proposed as an alternative fuel to fossil diesel. The aim of this research project is to optimally produce bio-oil in terms of quantity and quality from Jatropha curcas waste by using conventional and fast pyrolysis methods. Jatropha curcas shrub, which can be planted economically in tropical regions like Malaysia, is typically planted as a source of inedible oil for biodiesel production. The leftover pressed cake after oil extraction is an agricultural waste, which can be upgraded into fuel via pyrolysis. In this project, the pyrolysis parameters to achieve optimum quantity and quality of bio-oil from Jatropha curcas waste were determined. To achieve this, two fixed-bed pyrolysis rigs for conventional and fast pyrolysis processes were designed and fabricated, and a corresponding Design of Experiment was performed. By considering yield, calorific value, water content and acidity, the results from both methods were mathematically modelled after comparison and the optimum parameters for both methods were determined. The validated models of conventional and fast pyrolysis showed that optimum combined quantity and quality of bio-oil occur at reaction temperatures of 800 K and 747 K respectively but at the same nitrogen linear velocity of 0.0078 cm/s. At these optimum conditions, conventional and fast pyrolysis yield 50.08 wt% and 40.08 wt% of bio-oil with gross calorific values of 15.12 MJ/kg and 16.92 MJ/kg, water contents of 28.34 wt% and 28.02 wt%, and pH values of 6.77 and 7.01, respectively. The produced bio-oils from both rigs at their optimum points were dehydrated, and the physicochemical characteristics of the dehydrated bio-oils from both rigs were compared to standard specifications for burner biofuels. Based on ASTM D7554-10 standard for burner biofuel specifications, by reducing the sulphur contents, both dehydrated bio-oils can be used as burner fuel without any further processes. Finally, both 10% of optimised and dehydrated bio-oils emulsified in 90% diesel were tested and compared to EN590, the European standards for diesel used in commercial diesel engines and ASTM D6751-01, the standard biodiesel specifications. In addition to sulphur content, if the water content of both of these emulsified dehydrated bio-oils are removed, they can be commercially used as diesel fuel in diesel engines because their solid content, kinematic viscosity, ash content, flash point, cetane number and copper corrosion strip test results are within the range of EN590 standard.